Lollywood - Pakistani Cinema Through A Transitional Lens - Aslam, Erum Hafeez (JISR management and social sciences & economics, 2015)
The 68-year long history of Pakistani films has had its story of successes and failures. It has been a long time since films, as an industry, have been struggling to carve a niche for themselves. Recuperating from the blow of partition, films produced in Pakistan indicate that despite all odds, the local film industry has a lot of potential in every area of production: be it actors, directors, technicians, poets or script writers. Yet, for some reasons, successful combinations have not been able to sustain themselves long enough to contribute significantly. As a consequence, we have only been exposed to a few glimpses of rare productions. The objective of this study is to archive the historical evolution of Pakistani Cinema and give an overrview of the factors that have supposedly contributed to the rise and fall of the local film industry in different eras. This study follows the two-pronged approach. Both Qualitative Content Analysis and Literature Review are used as the methods of study. Firstly, five top grossing Pakistani films are sampled and content analyzed through popularity charts from each of the six decades under study. Subsequently, relevant literature, including newspapers and magazines articles, reviews and books are referred through online database to complement the analysis of the films. Convenient random sampling technique is used for the selection of the mainstream literature, reviewed. It is evident from the study that the lack of vibrant ideas, repetitive themes, the absence of modern facilities, industry's infighting besides illegal screening of Indian films on cable, new electronic channels and availability of pirated foreign films have led to the downfall of the Pakistani film industry. The study recommends that Lollywood should explore the niche market and develop itself on its cultural strength. The current boom of the Pakistani cinema demands a multifaceted approach to improve simultaneously quality, quantity and economics of the situation.